Evaluasi Penyaluran Vaksin Sesuai Standar CDOB (Cara Distribusi Obat yang Baik) - Kintan Fahra Ningrum; Iswandi Iswandi; Meta Kartika Untari (Journal Syifa Sciences and Clinical Research, 2022)
Vaccines are biological products made using germs and then weekened. According to existing studies, 75% of vaccines in Indonesia are exposed to freezing temperatures during the distribution process, as a result, vaccines cannot be used anymore. The City Health Office has responsibility for the distribution of vaccines, especially in health centers, which must be evenly distributed and given regularly at the right time. The purpose of this study is the distribution of cold chain vaccines from the City Health Office to Salatiga Health Centers using the 2020 CDOB regulatory guidelines. This study uses an observational method that has a descriptive nature and evaluation using data collection techniques by interviewing with pharmacists or vaccine managers. The data will be based on the analysis of the result of data collection using an interview sheet, and the results will be stated with a percentation. The results of the study indicate that the distribution guidelines for the rantai dingin vaccine distribution system from the Health Office to the Salatiga City Health Center using the 2020 CDOB have a good category with a percentage of 72,72% and 84,21%. Then, there was a discrepancy in the distribution carried out by the Health Service to the Salatiga City Health Center but no deviation occurred, the vaccine distributed was not damaged or expired. Factors that may occur due to discrepancies are the lack of Human Resources (HR) for vaccine managers and vaccine warehouses that have not been maximized.